2015
DOI: 10.1186/s40697-015-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Mass Screening for Chronic Kidney Disease in Rural and Remote Canadian First Nations People: Methodology and Demographic Characteristics

Abstract: BackgroundScreening the general population for Chronic Kidney Disease is not currently recommended.. Rural and remote Canadian First Nations people suffer a disproportionate burden of Kidney Failure. The First Nations Community Based Screening to Improve Kidney Health and Prevent Dialysis (FINISHED) project intends to test the hypothesis that a mobile, mass screening initiative available to all First Nations people 10 years of age and older residing in rural and/or remote communities, is feasible, will improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…The reasons for this are unknown, but may reflect the need for a better upstream approach and engagement for both the prevention of kidney disease (and type 2 diabetes) and its progression. In the indigenous population of Manitoba, 11 , 21 , 22 where higher rates of CKD were also reported, a greater severity of proteinuria was identified, a factor which would predict faster progression to end-stage renal disease. In Alberta, a higher incidence of end-stage renal disease was identified and predicted an increased risk of death.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The reasons for this are unknown, but may reflect the need for a better upstream approach and engagement for both the prevention of kidney disease (and type 2 diabetes) and its progression. In the indigenous population of Manitoba, 11 , 21 , 22 where higher rates of CKD were also reported, a greater severity of proteinuria was identified, a factor which would predict faster progression to end-stage renal disease. In Alberta, a higher incidence of end-stage renal disease was identified and predicted an increased risk of death.…”
Section: Discussionmentioning
confidence: 96%
“…Current efforts in Manitoba involve identifying opportunities for triage and screening within First Nations communities. 21 , 22 Komenda et al identified in the Finished Screening study that remote indigenous populations with less access to primary care demonstrated higher rates of treatable CKD. Replicating this model in Saskatchewan may identify geographic areas of highest need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both programs recruit individuals based on their risk factors for CKD, the KEEP concentrates their efforts on black populations, while the SeeKD considered other ethnic groups (Aboriginal, Hispanic, South Asian, Asian, and African) as being a risk factor for CKD (22). Targeting individuals from high-risk ethnic groups is not uncommon given the disproportionate burden of ESRD among different ethnic groups, and such screening programs have been established in Australia (23) and Canada (24). Further, the KEEP used a limited number of risk factors (personal history of diabetes or hypertension, or a family history of diabetes, hypertension, or kidney disease) (12,22,25) compared with the SeeKD program (diabetes, hypertension, existing kidney problems, family history of kidney disease, member of high-risk ethnic population, current vascular disease, or currently using tobacco products).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of eGFR and urinary albumin-tocreatinine ratio is now the accepted method of CKD staging (6) to better reflect risk of mortality and progression. Extensively validated risk prediction equations (14,15) using these same biomarkers can be readily integrated into point of care screening algorithms, providing real time feedback to patients on their personalized risk of progression to kidney failure (16).…”
mentioning
confidence: 99%